SUBYEK HUKUM (ORANG ATAU BADAN HUKUM) DALAM TINJAUAN HUKUM POSITIF DAN HUKUM ISLAM - Latua, Abidin (Jurnal GeoCivic, 2024)
Legal entities in the perspective of Islamic law are recognized as legal subjects. The subject of law (mahkum 'alaih) in Islamic law is themukallaf, namely a person who has fulfilled the requirements for competence to act legally (ahliyah al-ada'). Legal subjects based on positive law consist of persons (humans) and legal entities (rechtpersoon), where a legal actor must act and act with the conditions of competence as the law regulates. The position of legal entities as legal subjects is regulated in the Sharia Economic Law Compilation Chapter Legal Subjects.